Synthesis, characterization and quantum mechanical calculations of [Au 18Se8(dppthph)6]Cl2 - Neiß, Christian; et al. (European Journal of Inorganic Chemistry, 2007)
The reaction of [Au(tht)Cl] (tht = tetrahydrothiophene) with 2,5-bis(diphenylphophanyl)thiophene (dppthph) and Se-(SiMe) leads to the formation of [AuSe(dppthph) ]Cl. This compound crystallizes in two modifications, both containing a cluster dication with nearly identical gold-selenium cores. The dication consists of two subunits only connected by six aurophilic interactions. ESI MS demonstrates that these facilitate cohesion of the cluster subunits even in the gaseous state. SCS-MP2 calculations show that the dimer is a metasable species, which is ultimately prevented from dissociation by a Coulomb barrier. In addition, photoluminescene measurements demonstrate that the small differences in the ligand shell of the cluster molecules lead to different photoluminescene properties of the two modifications. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.